Detección de Patógenos a Través de Biosensores QCM (Microbalanza Cristal de Cuarzo). Revisión (2020)
This article exposes the electrical and physical behavior of sensor QCM (Quartz Crystal Microbalance) also known as TSM (Thickness Shear Mode), modifying and simulating variables as his Resonance Frequency and Inductance. Also is made a bibliographical revision of scientific articles where the sensor is used as a pathogen detector.